PENGARUH PENAMBAHAN ARANG TEMPURUNG KELAPA DENGAN INJEKSI FREKUENSI TINGGI TERHADAP KINERJA ELEKTRODA PELAT - Affan Rafli Andriansyah; Mochammad Dhofir; Tri Nurwati (Jurnal Mahasiswa TEUB, 2022)
The development of power systems in modern times places more demands on the safety, stability of power system operations. The grounding system is very important to ensure the safe and reliable operation of the power system to ensure the safety of people and the devices contained in a system when a fault occurs. This disturbance occurs when there is a short circuit current and fault current from lightning. Therefore, a system is needed to secure humans and electrical devices, namely a grounding system. Grounding system is a conductor connection system that connects systems, equipment bodies, and installations with earth/ground so as to protect humans and installations from the danger of abnormal currents. A good grounding system has a small resistance value. The resistance value is influenced by several factors, namely, the dimensions of the electrodes used, the configuration of the grounding system, the shape of the current and the frequency that flows, the chemical content of the soil. Soil treatment is one way to change the chemical composition of the soil by adding additives. In this study, an additive in the form of coconut shell charcoal was used and was given a high-frequency current injection with a range of 50-50kHz on plate type electrodes in vertical and horizontal planting configurations. The method used in this study is to use the 3 point method. The test results showed that the addition of coconut shell charcoal and the injection of high-frequency current affected the value of the real grounding impedance (resistance) in each planting configuration. The smallest real impedance value (resistance) obtained is when the grounding electrode is planted in a horizontal position and a 50kHz current is injected. When the electrode is injected a high frequency current indicates that the electrode is inductive while at the time the low frequency current is injected it is capacitive. Overall the value of real impedance (resistance) that can be reduced in each planting configuration is 20.98% to 49.79%.Keywords : Charcoal, Grounding, Impedance, Coconut Shell, Frequency